6ER-022 Clinical impact of the use of glucocorticoids for the treatment of COVID-19 in intermediate respiratory care units. Issue 1 (23rd March 2023) - Ayllón, M; Collada, VL; Villamañán, E; Escario, M; García, L; Herrero, A
Abstract : Background and Importance: During the pandemic, patients admitted to intermediate respiratory care units (IRCU) received non-invasive respiratory support and pharmacological treatment, mainly glucocorticoids (GC). Dexamethasone is the only one that has shown reducing mortality; however, there are no comparative efficacy studies between the different GC. Aim and Objectives: To determine the possible influence of the type and dose of GC on the patients' evolution with SARS-CoV-2 pneumonia admitted to the IRCU during the first and second wave of the pandemic. Material and Methods: Descriptive, observational and retrospective study of patients with SARS-CoV-2 infection admitted to the IRCU in a tertiary care hospital since March until December 2020. Demographic variables, comorbidities, GC therapy received and final resolution (improvement, transfer to ICU, or death) were analysed. The data were obtained from the clinical history and the electronic prescription. Results: 135 patients (62.5% men) were included with a mean age of 67.00 (SD:13.16) years. 69.31% of them had overweight and 29.41% respiratory pathologies. 89.63% of the patients admitted to the IRCU received treatment with GC, within them, 89 received treatment with a single GC, 27 received the combination of two and only 3 patients received three GC. 64 GC-treated patients improved, receiving a mean prednisone equivalent dose of 65.43 (SD:88.77) mg daily for a mean of 13.40 (SD:7.02) days. The 19 patients transferred to the ICU received a mean dose of 89.18 (SD:71.81) mg daily for 6, 00 (SD: 5.19) days. The 38 patients who died in IRCU treated with GC received a mean dose of 114.18 (SD: 90.39) mg daily for a mean of 8.92 (SD: 6.17) days. The most used GC or combinations were: dexamethasone (76 patients), dexamethasone and prednisone (13 patients), methylprednisolone (11 patients), dexamethasone and methylprednisolone (8 patients), and methylprednisolone and prednisone (5 patients). 100% of patients treated with dexamethasone and prednisone improved, followed by dexamethasone and methylprednisolone (62.5%) and methylprednisolone and prednisone (60%). 27.27% of the patients treated with methylprednisolone alone improved, with 63.64% dying. Conclusion and Relevance: Most of the patients admitted to the IRCU with coronavirus received GC and the results suggest some improvement in those who received lower doses of GC for longer periods. The GC combination was associated with a higher rate of improvement, especially with dexamethasone and prednisone. Treatment with methylprednisolone alone had the highest death rate. References and/or Acknowledgements: Conflict of Interest: No conflict of interest.